Obtaining paper from composition of different fibers and its analysis - Egamberdiev, E.; Turabdjanov, S.; Akmalova, G.; Mukhtarova, N.; Ayubova, I.; Mirzakhmedova, M.; Rakhmonberdiev, G. (E3S web of conferences, 2023)
Cellulose and paper products are produced from cotton wool in our republic. Since 1995, the production of these products has increased several times. Nevertheless, 10% of the demand for pulp and paper products in our Republic is met. uring 1988-1993, this growth was 6%, which was 3 times higher than wood pulp production. Extraction of cellulose from annual plants is well developed in China and India. 77% of the world's cellulose obtained from annual plants is produced in these countries. The People's Republic of China gets 50% of its paper output from annual plants. Cellulose was obtained from plants containing cellulose, and their properties were studied. Paper products were obtained from the resulting pulps and its quality indicators were studied based on the standards applied to papers used in industry.